2016
DOI: 10.1021/acsnano.6b03080
|View full text |Cite
|
Sign up to set email alerts
|

Rivet Graphene

Abstract: Large-area graphene has emerged as a promising material for use in flexible and transparent electronics due to its flexibility and optical and electronic properties. The anchoring of transition metal nanoparticles on large-area single-layer graphene is still a challenge. Here, we report an in situ preparation of carbon nano-onion-encapsulated Fe nanoparticles on rebar graphene, which we term rivet graphene. The hybrid film, which allows for polymer-free transfer and is strong enough to float on water with no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…A further reinforcement can be attained by performing a second CVD with Fe particles deposited on the rebar structure. 206 Rebar graphene with h-BN nanotubes have been also demonstrated, showing mechanical properties similar to those of the CNT rebar.…”
Section: Page 12 Of 53 Chemical Society Reviewsmentioning
confidence: 82%
“…A further reinforcement can be attained by performing a second CVD with Fe particles deposited on the rebar structure. 206 Rebar graphene with h-BN nanotubes have been also demonstrated, showing mechanical properties similar to those of the CNT rebar.…”
Section: Page 12 Of 53 Chemical Society Reviewsmentioning
confidence: 82%
“…On the other hand, using carbon cages as costing materials to protect clusters against external interference has been attracted a lot of attentions. [36][37][38][39][40][41] In particular, carbon cage encapsulating Si, Co, and Fe nanoparticles have been successfully synthesized by experiments, recently. [36][37][38][39][40] It has been shown that the carbon cage encapsulation not only acts as protective layer against cluster oxidation, the hybrid nanostructures formed by the carbon cage and the encapsulated nanoparticles can also exhibit interesting electronic structures and desirable properties for magnetic and battery applications.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39][40][41] In particular, carbon cage encapsulating Si, Co, and Fe nanoparticles have been successfully synthesized by experiments, recently. [36][37][38][39][40] It has been shown that the carbon cage encapsulation not only acts as protective layer against cluster oxidation, the hybrid nanostructures formed by the carbon cage and the encapsulated nanoparticles can also exhibit interesting electronic structures and desirable properties for magnetic and battery applications. [36][37][38][39][40][41] In the present paper, we propose a new design of Si-based nanostructures, i.e., carbon fullerene coated Si nanoclusters for improving the light absorption efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene was a kind of two-dimensional material which has been extensively investigated due to its outstanding performance in terms of high surface-to-volume ratio and outstanding electrical, optical, and mechanical properties [1][2][3][4]. A number of reports were focused on chemical sensing systems based on graphene materials such as chemiresistors [5,6], field-effect transistors [7,8], and other chemical sensors [9,10].…”
Section: Introductionmentioning
confidence: 99%